Ethanolic Extrusion of Indica Rice Flour for Rice Noodle Production - Miaomiao Fu; Xing Zhou; Hong (Sabrina) Tian; Yanxin Chen; Zhengyu Jin (Foods)
Due to the absence of gluten, rice noodles require complex processing to achieve a desirable texture. This study developed ethanolic-extruded indica rice flour (EERF) as a novel gluten substitute to simplify rice noodle production. EERF exhibited a distinct V-type crystalline structure (7.89% crystallinity) and high cold-paste viscosity (1043 cP), enabling its use as a binder in rice dough. When blended with native indica rice flour (IRF) at 10–20%, the EERF-IRF premix formed a cohesive dough with water via cold gelation, imparting viscoelasticity and tensile resistance. Optimal formulation (15% EERF for the premix and 37% water for making the dough) yielded fresh rice noodles with reduced cooking loss (5.57%) and a reduced breakage rate (14.44%), alongside enhanced sensory scores. This approach offers a clean-label, industrially scalable solution for producing rice noodles with simplified processing and improved quality.